Fibromyalgia treatment and management considerations for nurse practitioners - Stournaras, Dana; Petrovic, Kimberly (Journal of the American Association of Nurse Practitioners, 2019)
The purpose of this case study is to examine the role of the nurse practitioner in the management and treatment of a 35-year-old female patient diagnosed with several conditions, including fibromyalgia posttraumatic stress disorder, anxiety, and depression. Fibromyalgia is a chronic, nonprogressive rheumatic condition with cardinal symptoms of widespread pain and fatigue; it affects more than 5 million people in the United States. This case study examines the nurse practitioner's role in managing fibromyalgia. Benzodiazepines and opioids may be prescribed for treatment of symptoms but prove ineffective, thus contributing to dependency issues. Controversy exists over classification of fibromyalgia as a rheumatologic condition versus a mental health disorder. Fibromyalgia frequently is accompanied by anxiety and depression, making this illness difficult to diagnose and treat.
2 citations (Crossref) [2023-10-31] tex.eissn: 2327-6924 tex.unique-id: ISI:000480702800008
Keywords: Adult; Anxiety; Depression; Female; Fibromyalgia; Humans; Nurse Practitioners; Practice Patterns; Nurses'; Stress Disorders; Post-Traumatic; Treatment Outcome; adult; advanced practice nursing; anxiety; benzodiazepines; chronic disease; depression; dept.nur; female; fibromyalgia; hearing loss; human; nurse practitioner; nurse practitioners; nursing practice; opioids; pain; pathophysiology; peer-reviewed; posttraumatic stress disorder; psychology; role; role concept; treatment outcome